2012
DOI: 10.1007/s10833-012-9184-3
|View full text |Cite
|
Sign up to set email alerts
|

Toward an understanding of how teachers change during school reform: Considerations for educational leadership and school improvement

Abstract: As the concept of distributed leadership and its concomitant organizational structures become more prevalent in schools, studying how teacher capacity can be enhanced and can be used as a catalyst for reform is important. This article documents the nature of how the implementation of a research-validated reform influenced what teachers thought about their own teaching, student achievement, and expectations. A case study approach documented the experiences of elementary school teachers in a high poverty, histor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
30
0
7

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 33 publications
0
30
0
7
Order By: Relevance
“…These obstructions that block technology diffusion in the education system focus on two major aspects: organizational-management factors that reflect the need for pedagogical and technological adaptations required for ICT implementation, and factors that reflect personal aspects, e.g., teachers' perceptions and beliefs regarding ICT implementation in their own teaching (Hultman, 1995;Sung & Gibson, 2015;Teo, 2011). Also, there is a vague definition of what would be considered success in ICT implementation in education, causing tension and questions regarding the optimal implementation processes altogether (Kaniuka, 2012). Promoting as well as obstructing forces are influential on the ability to create processes of change and innovation within the education system (Cook, Holley, & Andrew, 2007;Liu, 2011), as this is an ongoing and lengthy process (Kotter & Cohen, 2012).…”
Section: Ict Implementation In the Education Systemmentioning
confidence: 99%
“…These obstructions that block technology diffusion in the education system focus on two major aspects: organizational-management factors that reflect the need for pedagogical and technological adaptations required for ICT implementation, and factors that reflect personal aspects, e.g., teachers' perceptions and beliefs regarding ICT implementation in their own teaching (Hultman, 1995;Sung & Gibson, 2015;Teo, 2011). Also, there is a vague definition of what would be considered success in ICT implementation in education, causing tension and questions regarding the optimal implementation processes altogether (Kaniuka, 2012). Promoting as well as obstructing forces are influential on the ability to create processes of change and innovation within the education system (Cook, Holley, & Andrew, 2007;Liu, 2011), as this is an ongoing and lengthy process (Kotter & Cohen, 2012).…”
Section: Ict Implementation In the Education Systemmentioning
confidence: 99%
“…Performing within multiple contexts-state, school district and parent associations, school principals' role is generally characterized by ambiguity, uncertainty, confusion, and misunderstanding, and all the more so, during periods of education reform. Embracing the dynamic tension between internal school goals and external reform demands is a central concern for principals, as it questions common practices and challenges the existing state of affairs (Kaniuka, 2012;Knapp & Feldman, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…For example, one of the main arguments is that inequities already exist in the varying levels of CCSS implementation: "The claim that CCSS implementation will be totally equitable is devalued because of the inherent variability within each of these approaches for teacher training, materials used, and experiences offered to students" (Liebtag, 2013, p.60). This argument is further supported in the literature where teachers are expected to implement new standards without having a solid understanding of what these mean in terms of transferring the language of the standards to actual learning objectives and classroom application (Jenkins & Agamba, 2013;Kaniuka, 2012;Spillane, Reiser, & Reimer, 2002). It must be noted that the new Common Core State Standards articulate the essentials, but lack direction on how to meet goals, how to connect the new standards into both teaching and student learning characterized by a lack of curriculum to support the implementation of the new standards: "The CCSS state than an intentional limitation was not to spell everything out.…”
Section: Background Of the Problemmentioning
confidence: 95%
“…From this perspective, how teachers interpret policy implementation depends to a great extent on teachers' prior knowledge and experience where, "Teacher learning is influenced not only by the opportunities that are available for learning but also the personal resources of the learner, including their prior knowledge, dispositions and beliefs" (Spillane, 1999, p.157). This idea is further extended by Kaniuka (2012), as it was found that teacher experience provided the prerequisite knowledge upon which teachers shaped their views on teaching, learning, and decision-making where their efficacy developed as a result of experience (p.341).…”
Section: Education Reform Implementationmentioning
confidence: 99%
See 1 more Smart Citation